Do we know what we think we know?: aid fragmentation and effectiveness revisited - Gehring, Kai; Michaelowa, Katharina; Dreher, Axel; Spörri, Franziska (Discussion papers, 2015)
Aid fragmentation is widely recognized as being detrimental to development outcomes. We re-investigate the impact of fragmentation on aid effectiveness in the context of growth, bureaucratic policy, and education, focusing on a number of conceptually different indicators of fragmentation, and paying attention to potentially heterogeneous effects across countries. Our results demonstrate the lack of robustness and any systematic pattern. This stresses the importance of questioning the sweeping conclusions drawn by much of the previous literature
Keywords: Arbeitspapier; Graue Literatur